New enzymes as potential therapeutic targets for trypanosomiases and leishmaniasis - Pereira, Claudio Alejandro (2011)
Infections caused by the protozoan parasites Trypanosoma cruzi, Trypanosoma brucei, and Leishmania spp. are among the most relevant public health problems in the developing countries.